Unacylated Ghrelin Enhances Satellite Cell Function and Relieves the Dystrophic Phenotype in Duchenne Muscular Dystrophy mdx Model. (7th May 2017) - Reano, Simone; Angelino, Elia; Ferrara, Michele; Malacarne, Valeria; Sustova, Hana; Sabry, Omar; Agosti, Emanuela; Clerici, Sara; Ruozi, Giulia; Zentilin, Lorena; Prodam, Flavia; Geuna, Stefano; et al.
Abstract : Muscle regeneration depends on satellite cells (SCs), quiescent precursors that, in consequence of injury or in pathological states such as muscular dystrophies, activate, proliferate, and differentiate to repair the damaged tissue. A subset of SCs undergoes self-renewal, thus preserving the SC pool and its regenerative potential. Unacylated ghrelin (UnAG) is a circulating hormone that protects muscle from atrophy, promotes myoblast differentiation, and enhances ischemia-induced muscle regeneration. Here we show that UnAG increases SC activity and stimulates Par polarity complex/p38-mediated asymmetric division, fostering both SC self-renewal and myoblast differentiation. Because of those activities on different steps of muscle regeneration, we hypothesized a beneficial effect of UnAG in mdx dystrophic mice, in which the absence of dystrophin leads to chronic muscle degeneration, defective muscle regeneration, fibrosis, and, at later stages of the pathology, SC pool exhaustion. Upregulation of UnAG levels in mdx mice reduces muscle degeneration, improves muscle function, and increases dystrophin-null SC self-renewal, maintaining the SC pool. Our results suggest that UnAG has significant therapeutic potential for preserving the muscles in dystrophies.